Technical guidance on the implementation of cooperation with overseas institutions for Takalar Regency Government staff - Aswin Baharuddin; Darwis; Munjin Syafik Asyari; Ishaq Rahman; Bama Andika Putra; Nurjannah Abdullah (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Although the substantively foreign policy is the authority of the central government, local governments must also deal with its implementation. Regional governments must anticipate opportunities to increase cooperation with parties abroad after the Government of Indonesia agrees on economic integration through the ASEAN Economic Community and other multilateral cooperation. In order to maximize these opportunities, the Takalar District Government must prepare government staff who will substantively and technically deal with the process. Responding to these problems, Hasanuddin University together with the Protocol and Communication Section of the Takalar Regency Government Leaders carried out a community service program. This activity aims to provide knowledge and technical skills to respond, analyze and assess cooperation between local governments and institutions abroad. The method used is technical guidance for the staff of the Takalar Regency Government. This activity is carried out in 4 stages, namely elaboration of priority issues with partners, training, mentoring and evaluation. This activity was attended by 15 staff from 5 work units. These work units include the Regional Secretariat, the Protocol and Communications Section of the Leaders, the Investment Office, the Regional Research and Development Agency, and the Cooperatives, MSMEs and Trade Office. The materials presented related to Globalization and Regional Autonomy, Diplomacy Transformation in the Digital Era and Procedures for Implementing Cooperation with foreign parties by Regional Governments were understood by 73.3 per cent of the participants.